Re-Evaluating China's Global Media Expansion. (21st June 2018) - Marsh, Vivien
As China continues its global economic rise, Chinese media have been tasked with making Beijing's official voice heard and understood in the world. Nine years after the launch of an accelerated 'media going-out' policy, however, the nature and impact of that policy are still contested even though by 2018, China's international media offering is vastly more sophisticated than that of 2009. As China becomes more assertive internationally, President Xi Jinping has reaffirmed the requirement for state media to act in the interests of the government and Communist Party at home and abroad. How much has changed? This editorial to the WPCC issue 'Re-Evaluating China's Global Media Expansion' outlines how contributors have extended the debate about China's media expansion focusing on the act of communicating the 'going-out' message and how it has been received by residents of Latin America, the USA and Africans studying in China. It considers the focus of these inquiries extending from television news to radio, from Twitter to the financial structures of Chinese internet firms along with book reviews of publications on Chinese and global media politics as well as noting opportunities for further research on China's global media expansion.